PWE-104 Peg site metastasis – an overstated problem? local experience of the pull through technique for peg insertion in head and neck cancer. (17th June 2017) - Rimmer, P; Hollywood, C; Mambro, A Di
Abstract : Introduction: Concerns regarding PEG site metastasis have resulted in a move away from the pull through insertion technique in head and neck cancer (HNC). 1 The BSG recommend a direct puncture technique, whilst others favour RIGs. 1 Recent data suggests the quoted risk of <1% could be overestimated. Continued use of the pull through technique may be justifiable. 2 Ultimately a lack of quality evidence prevents endorsement of one over another, however there is a significant cost difference in favour of the pull through technique. At Gloucestershire Hospitals NHSFT, the pull through technique continues to be employed for PEG insertion in HNC. We assessed its outcomes within our cohort. Method: Retrospective case analysis was done for all patients undergoing PEG via the pull through technique over 12 months between December 2014–2015. Data collected included demographics, 30 day and overall all-cause mortality. Stage, histology, treatment course, rates of recurrence and rates of PEG site metastasis were collected for HNC patients. To remain consistent with previous publications, data is expressed as the mean and standard error of the mean. To obtain longer term results, a focussed review of HNC patients was performed on audit data from 2013. Results: 115 PEGs were inserted over the initial period (Age 62.4±1.6 years). All-cause 30 day mortality was 6.1%, with no deaths directly caused by PEG insertion. 39 PEGs were inserted for HNC (Age 62.3±1.5). Patients were followed up for 531 days±31. The primary lesion was located in the oropharynx in 87%. There were no cases of PEG site metastasis. 3 patients subsequently developed distant metastases, with local recurrence in 7, equating to 26% overall recurrence rate. 30 day mortality in HNC patients was 2.6%. Overall Mortality was 26% at an average of 257±50 days post PEG. PEG removal was documented in 56%, at a mean of 249±28 days post insertion. A further 38 PEGs were inserted for HNC in 2013. 8 developed metastatic disease, whilst 3 had local recurrence. This equated to an overall recurrence rate of 29%. There were no cases of PEG site metastasis. 30 day mortality was 0%. 2 year mortality was 24%. Overall mortality increased to 39% with death at an average of 605 days±98.5. No deaths were attributed to PEG insertion. Conclusion: Mortality and disease recurrence outcomes for HNC are consistent with national statistics over short and long term follow up. 3 There were no cases of PEG site metastasis. Although our long term data is from a small cohort it supports the continued use of pull through technique as a safe and cost effective method of PEG insertion in HNC patients. References: . Westaby D, et al. Gut2010;59(12):1592–605. . Swinton M, et al. Gut 2016;65:A104. . HSCIC. National Head and Neck Cancer Audit 2013. Disclosure of Interest: None Declared